2023
DOI: 10.3390/ijms24076413
|View full text |Cite
|
Sign up to set email alerts
|

The Landscape of Accessible Chromatin and Developmental Transcriptome Maps Reveal a Genetic Mechanism of Skeletal Muscle Development in Pigs

Abstract: The epigenetic regulation mechanism of porcine skeletal muscle development relies on the openness of chromatin and is also precisely regulated by transcriptional machinery. However, fewer studies have exploited the temporal changes in gene expression and the landscape of accessible chromatin to reveal the underlying molecular mechanisms controlling muscle development. To address this, skeletal muscle biopsy samples were taken from Landrace pigs at days 0 (D0), 60 (D60), 120 (D120), and 180 (D180) after birth a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 65 publications
(69 reference statements)
0
7
0
Order By: Relevance
“…ACBD7 is a member of the multigene family containing Acyl-CoA binding domain (ACBD), which plays an important role in life activities such as energy metabolism and nutrient uptake [ 64 ]. ACBD7 can be regulated by transcription factors to promote muscle development and lipid metabolism, but cancer-related studies are lacking [ 65 ]. ACBD3, from the same family as ACBD7, has been found to be up-regulated in a variety of tumor tissues and may be responsible for poor breast cancer prognosis [ 66 , 67 ].…”
Section: Discussionmentioning
confidence: 99%
“…ACBD7 is a member of the multigene family containing Acyl-CoA binding domain (ACBD), which plays an important role in life activities such as energy metabolism and nutrient uptake [ 64 ]. ACBD7 can be regulated by transcription factors to promote muscle development and lipid metabolism, but cancer-related studies are lacking [ 65 ]. ACBD3, from the same family as ACBD7, has been found to be up-regulated in a variety of tumor tissues and may be responsible for poor breast cancer prognosis [ 66 , 67 ].…”
Section: Discussionmentioning
confidence: 99%
“…Transcriptome sequencing is a basic method to study the genes and functions related to muscle development in livestock and poultry, and has been widely used. Feng et al found key genes related to porcine skeletal muscle development through transcriptome analysis [ 8 ]. Li et al revealed the changes in gene expression between wild chickens and domestic chickens induced by domestication through transcriptome analysis of Gastrocnemius [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, it has gained significant traction in the exploration of cis-regulatory elements and the prediction of transcription factor binding sites [ 22 ]. Recently, ATAC-seq and RNA-seq techniques have been employed by researchers to investigate the skeletal muscle of various species including pigs and cows [ 23 , 24 ]. For instance, in Miao et al [ 25 ], ATAC-seq and RNA-seq techniques were used to analyze and study the difference in skeletal muscle growth and development between Luchuan pigs and Duroc pigs.…”
Section: Introductionmentioning
confidence: 99%